Clinical Implication and the Hereditary Factors of NM23 in Hepatocellular Carcinoma Based on Bioinformatics Analysis and Genome–Wide Association Study. (18th December 2018) - Yang, Chengkun; Han, Chuangye; Wang, Xiangkun; Liao, Xiwen; Liu, Xiaoguang; Qin, Wei; Yu, Long; Zhu, Guangzhi; Su, Hao; Lu, Sicong; Chen, Zhiwei; Yu, Tingdong; et al.
Abstract : NM23 expression is closely associated with hepatocellular carcinoma (HCC) recurrence, but the hereditary factors influencing NM23 levels are unknown. Using public database, the diagnostic value of NM23 in HCC was investigated. A total of 424 hepatitis B virus- (HBV-) related HCC patients were enrolled to perform a genome–wide association study for identifying candidate variants associated with NM23 expression level. Additionally, a logistic regression model, haplotypes, and survival analysis were performed in the subsequent analysis. We identified high NM23 expression levels that have a diagnostic accuracy in HCC tissues and had a poor recurrence-free survival in HBV-related HCC patients. Variants near Psoriasis susceptibility 1 candidate 1 ( PSORS1C1 ) and StAR related lipid transdomain containing 3 ( STARD3 ) are associated with NM23 expression. The PSORS1C1 haplotype TGCACA and the STARD3 haplotype GG have favorable cumulative effects on NM23 expression. Further, variants in PSORS1C1 were associated with either overall survival (rs556285588, rs3095301, and rs3131003) only or overall survival and recurrence-free survival (rs560052000 and rs541820233) both in HCC patients. Our findings suggested that variants at the PSORS1C1 and STARD3 loci play an important role in NM23 regulation. Moreover, variants in PSORS1C1 are potential biomarkers for the prediction of postoperative clinical outcomes in HBV-related HCC patients. Thus, variants in PSORS1C1 and STARD3 are associated with NM23 expression and clinical outcomes of HBV-related HCC patients, which may be regarded as potential biomarkers for this disease.